1986
DOI: 10.1007/bf02774491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pure pancreatic juice proteins by two-dimensional gel electrophoresis in cases of pancreatic cancer

Abstract: To clarify the difference in the protein composition of pancreatic juice between patients with pancreatic cancer and normal controls, the proteins of pure pancreatic juice from three cases of cancer of the head of the pancreas and six apparently healthy adults were analyzed by two-dimensional gel electrophoresis (two-DE) followed by silver staining. Two minor proteins of Mr 59,000 and Mr 78,000 present in all the three patients were not detected in the six controls. We have identified the minor proteins with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 27 ] Furthermore, it was reported that TF was increased in the pancreatic juice of the patients with pancreatic cancer, as compared with apparently healthy adults. [ 28 ] Based on findings of our study, we guess that TF is secreted to pancreatic juice rather than blood in patients with PDAC. The finding that TF expression correlated with differentiation of the tumor and the survival further confirmed the importance of this protein in association with PDAC.…”
Section: Discussionmentioning
confidence: 91%
“…[ 27 ] Furthermore, it was reported that TF was increased in the pancreatic juice of the patients with pancreatic cancer, as compared with apparently healthy adults. [ 28 ] Based on findings of our study, we guess that TF is secreted to pancreatic juice rather than blood in patients with PDAC. The finding that TF expression correlated with differentiation of the tumor and the survival further confirmed the importance of this protein in association with PDAC.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, many cancers share the same markers e.g. CEA, CA19-9, transferrin and alpha1-antitrypsin [40,42,64].…”
Section: Principal Component Analysis Plot Of Proteomic Features Of Tmentioning
confidence: 99%
“…Among these proteins, we noticed that three proteins, Cp, Apo-E, and Tf, had relative higher protein scores according to nanoLC-MS/MS analysis and their molecular weights (MWs) were well-corresponded with the bands in the gel ( Figure 3 a). Cp, Apo-E, and Tf were reported as pivotal oncogenic proteins involved in the progression of PC and have the potential for PC diagnosis [ 22 , 23 , 27 , 28 ]. Therefore, we further analyzed the level of Cp, Apo-E, and Tf in PHA-E pulled-down serum proteins by using their specific antibodies though Western blotting.…”
Section: Resultsmentioning
confidence: 99%